Analisis Strategi Komunikasi Dalam Pemasaran Global - Arjuna Arjuna; M. Alfito Dinova; Ansor Nasution; Suhairi Suhairi (Universitas 45 Surabaya, 2024)
This article contains about how to implement marketing strategies in the world of global or international markets in Indonesia. As we know that Worldwide Promotion is the act of displaying by worldwide organizations having worldwide organizations with worldwide advertising techniques, worldwide business sectors and worldwide products and guidelines in different countries. Globalization is another test for organizations in implementing promotion methodologies. Due to globalization, organizations are required to compete with organizations that have large capital and quality goods. To date, Indonesia is a hotly contested target market. Globalization and market competition require all leaders to focus on the world climate. This review aims to find a worldwide advertising methodology in the Indonesian market for Indonesian organizations. The examination strategy used is an expressive investigative technique. The combination of a variety of display procedures and standard promotion techniques is a worldwide advertising methodology that is appropriate to the economic situation in Indonesia.